2022
DOI: 10.3389/fpls.2022.962246
|View full text |Cite
|
Sign up to set email alerts
|

Microbial mechanism of zinc fertilizer input on rice grain yield and zinc content of polished rice

Abstract: Zinc is an essential minor element for rice growth and human health, which can also change the structure of the microorganisms. However, it remains unclear for the effects of zinc fertilizer on microbiome function in agricultural soils and crops. To solve this research gap, we investigated the relationship between improving rice (Oryza sativa L.) yield, Zn concentration, soil microbial community diversity, and function by the application of Zn fertilizer. The field trials included three rice varieties (Huanghu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 74 publications
3
3
0
Order By: Relevance
“…Previous studies have reported that micronutrients explained a large variation in the structure of microbial communities in agricultural soils receiving specific micronutrients 20 , while we further confirm the relationship between micronutrients and microbial structure in a wider range of soils with more contrasting properties and under different land uses. Our finding is also consistent with some experiments showing that iron minerals shaped soil microbial community 21 and Zn fertilization decreased soil microbial diversity and altered community composition in paddy soil 22 . In general, soil pH is previously reported to be positively linked to soil bacterial diversity 4 , 23 and also negatively linked to micronutrient availability 24 .…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that micronutrients explained a large variation in the structure of microbial communities in agricultural soils receiving specific micronutrients 20 , while we further confirm the relationship between micronutrients and microbial structure in a wider range of soils with more contrasting properties and under different land uses. Our finding is also consistent with some experiments showing that iron minerals shaped soil microbial community 21 and Zn fertilization decreased soil microbial diversity and altered community composition in paddy soil 22 . In general, soil pH is previously reported to be positively linked to soil bacterial diversity 4 , 23 and also negatively linked to micronutrient availability 24 .…”
Section: Discussionsupporting
confidence: 93%
“…We hypothesized that the Zn ions in the framework are contributing to the enhanced performance that we observed with plain ZIFs. This is consistent with the previous research showing the yield-promoting impacts of nanoscale metal and micronutrient treatments in other crops. , In addition, zinc fertilizers have been recently shown to alter the microbial communities in the rhizosphere, which promotes plant growth and eventually increases yield …”
Section: Impact Of Mizifs On Crop Growth and Nutritional Valuesupporting
confidence: 92%
“…Bio-fertilizer such as Rhizobacter, Azopirillum, and Bacillus sp are Zn-solubilizing bacteria that can enhance the content of Zn under a watered condition and significantly improve crop growth, yield, and Zn content. The varied Zn content in rice mutant lines by treatments was also previously reported [13]. The Zn content in grain is largely determined by genotype rather than by Zn fertilizer, which could be attributed to differences in Zn uptake behavior.…”
Section: Resultssupporting
confidence: 71%
“…Soil microbes metabolize recalcitrant forms of soilborne nutrients to liberate these elements for plant nutrition [11]. Most nutrients are bound to organic molecules and are therefore minimally available for soil microbes such as bacteria and fungi, which possess the metabolic machinery to depolymerize and mineralize organic compounds [12,13]. The contents of these microbial cells are subsequently released, either through turnover or cell lysis.…”
Section: Introductionmentioning
confidence: 99%